Synaptically induced sodium signals in hippocampal astrocytes in situ - Langer, Julia (Blackwell Science Inc, 2009)
Astrocytes are in close contact to excitatory synapses and express transporters which mediate the sodium-dependent uptake of glutamate. In cultured astrocytes, selective activation of glutamate transport results in sodium elevations which stimulate Na(+)/K(+)-ATPase and glucose uptake, indicating that synaptic release of glutamate might couple excitatory neuronal activity to glial sodium homeostasis and metabolism. Here, we analysed intracellular sodium transients evoked by synaptic stimulation in acute mouse hippocampal slices using quantitative sodium imaging with the sodium-sensitive fluorescent indicator dye SBFI (sodium-binding benzofuran isophthalate). We found that short bursts of Schaffer collateral stimulation evoke sodium transients in the millimolar range in both CA1 pyramidal neurons and in SR101-positive astrocytes of the stratum radiatum. At low stimulation intensities, glial sodium transients were confined to one to two primary branches and adjacent fine processes and only weakly invaded the soma. Increasing the number of activated afferent fibres by increasing the stimulation intensity elicited global sodium transients detectable in the processes as well as the somata of astrocytes. Pharmacological analysis revealed that neuronal sodium signals were mainly attributable to sodium influx through ionotropic glutamate receptors. Activation of ionotropic receptors also contributed to glial sodium transients, while TBOA-sensitive glutamate transport was the major pathway responsible for sodium influx into astrocytes. Our results thus establish that glutamatergic synaptic transmission in the hippocampus results in sodium transients in astrocytes that are mainly mediated by activation of glutamate transport. They support the proposed link between excitatory synaptic activity, glutamate uptake and sodium signals in astrocytes of the hippocampus.